The mannose receptor negatively modulates the Toll-like receptor 4–aryl hydrocarbon receptor–indoleamine 2,3-dioxygenase axis in dendritic cells affecting T helper cell polarization - Salazar, Fabián; Hall, Laurence; Negm, Ola H.; Awuah, Dennis; Tighe, Patrick J.; Shakib, Farouk; Ghaemmaghami, Amir M. (Elsevier, 2016)
Background: Dendritic cells (DCs) are key players in the induction and re-elicitation of TH2 responses to allergens. We have previously shown that different C-type lectin receptors on DCs play a major role in allergen recognition and uptake. In particular, mannose receptor (MR), through modulation of Toll-like receptor (TLR) 4 signaling, can regulate indoleamine 2,3-dioxygenase (IDO) activity, favoring TH2 responses. Interestingly, the aryl hydrocarbon receptor (AhR), a ligand-dependent transcription factor with an emerging role in immune modulation, has been implicated in IDO activation in response to TLR stimulation. Objective: Here we investigated how allergens and lectins modulate the TLR4-AhR-IDO axis in human monocyte-derived DCs. Methods: Using a combination of genomics, proteomics, and immunologic studies, we investigated the role of MR and AhR in IDO regulation and its effect on T helper cell differentiation. Results: We have demonstrated that LPS induces both IDO isoforms (IDO1 and IDO2) in DCs, with partial involvement of AhR. Additionally, we found that, like mannan, different airborne allergens can effectively downregulate TLR4-induced IDO1 and IDO2 expression, most likely through binding to the MR. Mannose-based ligands were also able to downregulate IL-12p70 production by DCs, affecting T helper cell polarization. Interestingly, AhR and some components of the noncanonical nuclear factor κB pathway were shown to be downregulated after MR engagement, which could explain the regulatory effects of MR on IDO expression. Conclusion: Our work demonstrates a key role for MR in the modulation of the TLR4-AhR-IDO axis, which has a significant effect on DC behavior and the development of immune responses against allergens.